7 Outcomes of medically-treated patients with M2-segment middle cerebral artery occlusion. Results from the prospective multicentral international cohort study INTERRSeCT. (July 2018) - Menon, B; Najm, M; Al-Ajlan, F; Almekhlafi, M; Puig, J; Castellanos, M; Dowlatshahi, D; Calleja, A; Sohn, S; Ahn, S; Poppe, A; Mikulik, R; et al.
Abstract : Background: Patients with proximal arterial M2-segment of the Middle Cerebral Artery (M2-MCA) occlusions were largely excluded from endovascular stroke trials. Current American Stroke guidelines are conservative in recommending thrombectomy for such patients. We sought to assess the natural history of medically- treated M2-MCA occlusion patients. Methods: This is a prospective multi-central international cohort study of all acute ischemic stroke patients with intracranial occlusions on baseline imaging. Patients with M2-MCA occlusions were identified on baseline CT angiography and non-endovascular-treated patients were included. The M2-MCA segment was defined as the first-order branch of the proximal MCA, excluding the anterior temporal artery. The M2-MCA was further classified according to its visually-assessed diameter relative to the M1-MCA into: M1-equivalent (>90% of the diameter of the M1-MCA), Major (50%–90%), Minor (<50%). Follow-up CTA 4 hours from baseline imaging was used to assess recanalization using the revised arterial occlusive lesion (rAOL). Results: Out of 575 patients in the entire study, there were a total of 184 M2-MCA occlusions seen. Of those, 104 patients were NOT treated with endovascular therapy: 90 patients (86.5%) received IV TPA and 14 (23.5%) patients conservative management. Among those, 23.1% (24/104) M1-equivalent, 66.4% (69/104) major, and 9.6% (10/104) minor M2-MCA. The median age was 76 years (interquartile range 19 years). The median (IQR) baseline NIHSS score of the cohort was 9 (9): M1-equivalent 12(10), major 9 (9), minor 7 (8). The median baseline ASPECTS was 9 overall and in all M2 groups. Successful recanalization was observed in 44.2% (46/104) of the medical M2 occlusion cohort overall. TPA group was 47.8% (43/90) and conservative group 21.4% (3/14). With IV TPA successful recanalization occurred in 30% (6/20) of M1-equivalent, 50% (31/62) of major, and 75% (6/8) of minor M2-MCA occlusions. In conservative management group successful recanalization occurred in 25% (1/4) of M1-equivalent, 14.3% (1/7) of major, and 50% (1/2) of minor M2-MCA occlusions. Good functional outcome (mRS 0–2) at 90 day was observed in 62.1% (64/104) of the cohort overall. Among those with successful recanalization, 76.1% (35/46) achieved good outcome. With IV TPA, the proportion of patients achieving independent functional outcome was 45% (9/20) with M1-equivalent, 70.5% (43/61) of major, and 62.5% (5/8) of minor M2-MCA occlusions. In the conservative management group, the proportion of patients achieving independent functional outcome at 90 day was 25% (1/4) with M1-equivalent, 71.4% (5/7) of major, and 50% (1/2) of minor M2-MCA occlusions. In logistic regression analyses, successful recanalization predicted independent functional outcome (OR 2.9, 95% CI 1.02 to 8.1, p 0.046). Age (OR 0.89, 95% CI 0.84 to 0.94, p<0.001) and baseline NIHSS (OR 0.90, 95% CI 0.83 to 0.97, p 0.009) were negative predictors of good outcomes. Conclusion: While over one half of medically-treated patients with M2-MCA segment occlusions achieve independent outcome, a subset of patients suffers poor functional outcomes at 90 days. Successful recanalization are associated with higher odds of independent functional outcome. Disclosures: B. Menon: None. M. Najm: None. F. Al-Ajlan: None. M. Almekhlafi: None. J. Puig: None. M. Castellanos: None. D. Dowlatshahi: None. A. Calleja: None. S. Sohn: None. S. Ahn: None. A. Poppe: None. R. Mikulik: None. N. Asdaghi: None. T. Field: None. A. Jin: None. T. Asil: None. J. Boulanger: None. E. Smith: None. S. Coutts: None. P. Barber: None. S. Bal: None. S. Subramanian: None. S. Mishra: None. A. Trivedi: None. S. Dey: None. M. Eesa: None. T. Sajobi: None. M. Goyal: None. M. Hill: None. A. Demchuk: None.